Successfully reported this slideshow.
We use your LinkedIn profile and activity data to personalize ads and to show you more relevant ads. You can change your ad preferences anytime.

Factorising algebraic expressions

8,106 views

Published on

A slideshow to explain the process of factorising algebraic expressions.

Published in: Education, Technology

Factorising algebraic expressions

  1. 1. Factorising Algebraic Expressions<br />
  2. 2. This is factorising…<br />8<br /> <br />=4×2<br /> <br />=8×1<br /> <br />6𝑎<br /> <br />=6×𝑎<br /> <br />=6𝑎×1<br /> <br />𝑚2<br /> <br />=𝑚×𝑚<br /> <br />12𝑦2<br /> <br />=3×4𝑦2<br /> <br />=4𝑦×3𝑦<br /> <br />
  3. 3. This is an algebraic expression:<br />2𝑎+6<br /> <br />Algebraic expressions can sometimes be factorised.<br />2×(𝑎+3)<br /> <br />=<br /> <br />2𝑎+6<br /> <br />=<br /> <br />2(𝑎+3)<br /> <br />
  4. 4. 𝑎<br /> <br />𝑎<br /> <br />6<br /> <br />+<br /> <br />2𝑎<br /> <br />
  5. 5. 𝑎+3<br /> <br />𝑎+3<br /> <br />2×(𝑎+3)<br /> <br />2(𝑎+3)<br /> <br />Factorised algebraic expression<br />
  6. 6. 2𝑎+6<br /> <br />Factors of  𝟐𝒂<br /> <br />Factors of  𝟔<br /> <br />3, 2, 1, 6<br /> <br />2, 1, 𝑎<br /> <br />𝐻𝐶𝐹=2<br /> <br />=2×𝑎<br /> <br />+ 2×3<br /> <br />2𝑎+6<br /> <br />=2×(𝑎+3)<br /> <br />=2(𝑎+3)<br /> <br />
  7. 7. 8𝑚+12<br /> <br />Factors of  𝟖𝒎<br /> <br />Factors of  𝟏𝟐<br /> <br />3, 4, 2, 6, 1, 12<br /> <br />1, 8, 2, 4, 𝑚<br /> <br />𝐻𝐶𝐹=4<br /> <br />+ 4×3<br /> <br />=4×2𝑚<br /> <br />8𝑚+12<br /> <br />=4×(2𝑚+3)<br /> <br />=4(2𝑚+3)<br /> <br />
  8. 8. 5𝑎𝑏+10𝑎<br /> <br />Factors of  𝟓𝒂𝒃<br /> <br />Factors of  𝟏𝟎𝒂<br /> <br />2, 5, 1, 10, 𝑎<br /> <br />1, 5, 𝑎, 𝑏<br /> <br />𝐻𝐶𝐹=5𝑎<br /> <br />+ 5𝑎×2<br /> <br />=5𝑎×𝑏<br /> <br />5𝑎𝑏+10𝑎<br /> <br />=5𝑎×(𝑏+2)<br /> <br />=5𝑎(𝑏+2)<br /> <br />
  9. 9. 9𝑗𝑘+4𝑘<br /> <br />Factors of  𝟗𝒋𝒌<br /> <br />Factors of  𝟒𝒌<br /> <br />1, 4, 𝑘<br /> <br />1, 9, 𝑗, 𝑘<br /> <br />𝐻𝐶𝐹=𝑘<br /> <br />+ 𝑘×4<br /> <br />=𝑘×9𝑗<br /> <br />9𝑗𝑘+4𝑘<br /> <br />=𝑘×(9𝑗+4)<br /> <br />=𝑘(9𝑗+4)<br /> <br />
  10. 10. 𝐻𝐶𝐹=3<br /> <br />12h+3<br /> <br />=3×4h+3×1<br /> <br />+<br /> <br />=3(4h+1)<br /> <br />4h<br /> <br />1<br /> <br />𝐻𝐶𝐹=𝑏<br /> <br />𝑎𝑏−4𝑏<br /> <br />=𝑏×𝑎−𝑏×4<br /> <br />=𝑏(𝑎−4)<br /> <br />𝑎<br /> <br />4<br /> <br />−<br /> <br />

×